Phenotypic and Molecular Analysis of Transgenic Tobacco with Rabies Glycoprotein for Stability of Gene Expression - Gowda2, N. Nagesha1*; P.H. Ramanjini (Journal of Phytology, 2011)
The agronomic and morphological characteristics of Agrobacterium mediated transformed plants carrying the ERA strain of the rabies glycoprotein gene in different progenies of tobacco (FCV var.) were investigated. Significant variation in plant height and the leaf area was observed in all the generations of the plants. However no significant differences were observed for number of leaves per plant. Most of the variations in R1 to R4 plants have no significant correlation with transgene insertion and were proved heritability characters in the progenies. None of the plants in R1 to R4 generation showed any dwarfism or stunted growth. The molecular analysis of the transgenic tobacco progenies did not show any significant differences in the expression of rabies glycoprotein, thus indicating the stability of the gene expression.